SISCO 2.0: fostering understanding in disability awareness for a more inclusive future - Abd Rahman, Nurul Hayani; Alias, Roslinda; Harun, Rabitah; Abd Rahman, Nurul Fazila (Universiti Teknologi MARA, Kedah, 2024)
The UiTM Kedah Branch implemented Siswa Cakna OKU (SISCO) 2.0 in 2023 as one of its community service programs, with the aim of educating students about disabilities and indirectly promoting empathy and understanding. This program can help reduce stigma and discrimination and create a more inclusive future. On December 7, 2023, the second edition of SISCO took place. This community service program involved participants from various categories, including students from Sekolah Menengah Pendidikan Khas Vokasional Merbok and Kolej Komuniti Sungai Petani, as well as UiTM Kedah Branch students from different study programs. In addition, there was support from Perpustakaan Sultan Badlishah, Jabatan Kebajikan Masyarakat (JKM), Unit Perkhidmatan OKU (UPO) UiTM, and the Student Affairs Division, UiTM Kedah Branch. Students registered for HPD233, one of the co-curriculum courses offered for diploma students in the October 2023 semester, designed activities that addressed the seven recognized types of disabilities in Malaysia. Among other things, education systems must implement positive support systems that cater to the specific challenges faced by students with disabilities and increase disability awareness. A lack of awareness and understanding of the needs of persons with disabilities may result in discrimination and a failure to provide appropriate and reasonable accommodations. Thus, inclusive education policies that address individual learning needs and provide necessary accommodations can foster a supportive learning environment.